Dexamethasone versus prednisone for children receiving asthma treatment in the paediatric inpatient population: protocol for a feasibility randomised controlled trial. Issue 12 (14th December 2018) - Pound, Catherine M; McDonald, Jaime; Tang, Ken; Seidman, Gillian; Jetty, Radha; Zaidi, Sarah; Plint, Amy C
Abstract : Introduction: Asthma exacerbations are a leading cause of paediatric hospitalisations. Corticosteroids are key in the treatment of asthma exacerbations. Most current corticosteroids treatment regimens for children admitted with asthma exacerbation consist of a 5-day course of prednisone or prednisolone. However, these medications are associated with poor taste and significant vomiting, resulting in poor compliance with the treatment course. While some centres already use a short course of dexamethasone for treating children hospitalised with asthma, there is no evidence to support this practice in the inpatient population. Methods and analysis: This single-site, pragmatic, feasibility randomised controlled trial will determine the feasibility of a non-inferiority trial, comparing two treatment regimens for children admitted to the hospital and receiving asthma treatment. Children 18 months to 17 years presenting to a Canadian tertiary care centre will be randomised to receive either a short course of dexamethasone or a longer course of prednisone/prednisolone once admitted to the inpatient units. The primary clinical outcome for this feasibility study will be readmission to hospital or repeat emergency department visits, or unplanned visits to primary healthcare providers for asthma symptoms within 4 weeks of hospital discharge. Feasibility outcomes will include recruitment and allocation success, compliance with study procedures, retention rate, and safety and tolerability of study medications. We plan on recruiting 51 children, and between-group comparisons of the clinical outcome will be conducted to gain insights on probable effect sizes. Ethics and dissemination: Research Ethics Board approval has been obtained for this study. The results of this study will inform a multisite trial comparing prednisone/prednisolone to dexamethasone in inpatient asthma treatment, which will have the potential to improve the delivery of asthma care, by improving compliance with a mainstay of treatment. Results will be disseminated through peer-reviewed publications, organisations and meetings. Trial registration number: NCT03133897 ; Pre-results.